2018
DOI: 10.1097/01.blo.0000533628.06091.0a
|View full text |Cite
|
Sign up to set email alerts
|

Can Shoulder Muscle Activity Be Evaluated With Ultrasound Shear Wave Elastography?

Abstract: Shear wave electrography can be used to measure various tissue elasticities in both static and dynamic modes. It may be a useful tool to evaluate pre- and postoperative rotator cuff muscle activity in a relatively simple manner. Shoulder function after reverse total shoulder arthroplasty associated with deltoid muscle activity also may be evaluated. Changes in tissue tightness in shoulder disorders caused by increase soft tissue stiffness (ie, adhesive capsulitis and glenohumeral internal rotation deficit) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…For skeletal muscles, we recommend the SWV as a surrogate for muscle elasticity instead of the Young's modulus. This will help with reliability of study results and allow more accurate comparison between studies [18,32,34]. Reviewing the literature on muscle SWE, we found that most studies performed SWE in a shoulder abduction position because of the time limitations.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For skeletal muscles, we recommend the SWV as a surrogate for muscle elasticity instead of the Young's modulus. This will help with reliability of study results and allow more accurate comparison between studies [18,32,34]. Reviewing the literature on muscle SWE, we found that most studies performed SWE in a shoulder abduction position because of the time limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Particularly, gender had impact on MD elasticity at both L0° (P< 0.05) and R0° (P< 0.01) in the present study, maybe indicating there is a signi cant difference in the MD elasticity between genders during shoulder 0° abduction. A possible explanation for this discrepancy may be the obvious difference in the MD muscle size and composition between genders at shoulder 0° abduction [16][17][18][19][20]. Haizlip et al [21] showed that collagen and elastin architectures of muscle bers mainly determined MD elasticity, which may vary between different gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new technique called SWE can quantitatively re ect biomechanics changes of muscles contractility. Increased muscle elasticity during shoulder active abduction, resulting from muscle contraction, is an especially exciting area for clinical integration of ultrasound elastography [6,12,24]. Firstly, it may be the rst study to quantitatively assess normal MD elasticity by measuring the SWV during different shoulder active abduction.…”
Section: Discussionmentioning
confidence: 99%
“…Shear wave elastography (SWE) as a new ultrasound-based elastography technique, quantitatively providing the biomechanics parameters of the muscles such as muscle elasticity, has good repeatability and reproducibility [10][11]. Excellent reliability and feasibility for assessing the deltoid using SWE were reported [4,[12][13]. SWE can quantitatively evaluate muscle elasticity through elastic parameters such as shear wave velocity (SWV) and Young's modulus [10,14].…”
Section: Introductionmentioning
confidence: 99%